1997
DOI: 10.1093/qjmed/90.5.359
|View full text |Cite
|
Sign up to set email alerts
|

Acute bone-marrow oedema in cyclosporin-treated renal transplant recipients

Abstract: Transient musculoskeletal pain may occur in renal transplant patients on cyclosporin (CyA). Of 28 consecutive patients transplanted in this unit between 20 January 1995 and 2 May 1996, eight (two published elsewhere) developed this problem. Before transplantation, three of the patients had received prednisone intermittently or continuously for 15, 5 and 2 years, for asthma, crescentic GN and SLE, respectively. All patients had normal hand radiographs prior to transplantation. Five developed acute rejection fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 5 publications
1
12
1
Order By: Relevance
“…10,15-17 However, magnetic resonance imaging of the affected area commonly shows bone marrow ede-ma. 8,9,15,16,18 In our patient, there was mild signal abnormality in the epiphyses around the knees that may have represented bone marrow edema, but it was not as prominent as cases illustrated in the literature. 8, 19 What was most striking in our patient was the presence of high signal intensity in the periosteal regions of the femora and tibiae, a finding not highlighted previously in the literature but one that has been shown to accompany bone marrow edema.…”
Section: Discussioncontrasting
confidence: 58%
“…10,15-17 However, magnetic resonance imaging of the affected area commonly shows bone marrow ede-ma. 8,9,15,16,18 In our patient, there was mild signal abnormality in the epiphyses around the knees that may have represented bone marrow edema, but it was not as prominent as cases illustrated in the literature. 8, 19 What was most striking in our patient was the presence of high signal intensity in the periosteal regions of the femora and tibiae, a finding not highlighted previously in the literature but one that has been shown to accompany bone marrow edema.…”
Section: Discussioncontrasting
confidence: 58%
“…It has been suggested that this disorder is a part of a spectrum of disorders affecting bone that includes reflex sympathetic dystrophy and transient osteoporosis. A number of previous studies have documented similar bone marrow edema patterns in the femoral head (14,15). Jagose et al (14) reported eight cases, including four who had knee involvement.…”
Section: Discussionmentioning
confidence: 78%
“…However, cartilage thinning (as a manifestation of degenerative disease) was not a feature in many cases, and this fact makes it less likely that degenerative disease or focal chondral injury was the sole cause of the observed abnormalities. One probable cause of subchondral marrow abnormality may be a combination of steroid-induced subchondral bone demineralization and increased physical activity after recovery from SARS, which could lead to subchondral trabecular impaction and edema similar to those described in patients after renal transplantation (11,12,(22)(23)(24)(25). Another probable cause of subchondral marrow abnormality is early subchondral osteonecrosis (9).…”
Section: Discussionmentioning
confidence: 97%